SAIMI Study - Health and Health Care Access by Immigrants from the Indian Subcontinent in Lisbon: What Recommendations for Equitable and Culturally Adequate Health Care? - Campos Matos, Inês (2015)
Introduction: The growth of the immigrant population in Portugal has been consistent over the past decades. Nevertheless, information on the health of immigrant populations is scarce. This research uses data collected from the population from the Indian subcontinent living in the district of Lisbon to produce recommendations for the provision of culturally adapted health services.Material and Methods: Cross-sectional study with the immigrant community of the Indian subcontinent (Bangladesh, India and Pakistan) living in Lisbon, selected based on a snowball sampling technique and using privileged access interviewers. The questionnaire focused on health, health care access, lifestyle and attitudes towards death. The data were subject to a descriptive analysis and anage-standardized comparison between the three nationalities was made.Results: Surveys were administered to 1011 individuals with a participation rate of 97%. Most participants were adult males. Indian immigrants most frequently reported barriers to use of health services and had a higher frequency of chronic diseases. Pakistani immigrants had worse lifestyle indicators.Discussion: The immigrant population from the Indian subcontinent tends to report more language difficulties in health care access when compared with other immigrant populations. Based on recommendations of the World Health Organization, it was possible to adapt this knowledge to produce recommendations adapted to the Portuguese context.Conclusion: There are several aspects in the management of health services in Portugal that can be better adapted to the immigrant population from the Indian subcontinent.